Spiritual education of an individual – general objective of secondary and higher education - Šernas, Vytautas (Acta Paedagogica Vilnensia, 1999)
Teacher is the heart and soul of the educational process, the cultivator of life wisdom and national culture. He is the guide into the riches of mother tongue, national and foreign literature, science and technology. Teacher is not only the carrier of knowledge which is quickly forgotten, but the one who implants perennial values in the consciousness of the pupils, educates moral persons, not indifferent to the sufferings and achievements of the people of his own country. Spiritual education of pupils and students is a deep and complex problem. Its solution depends on the successful training of spiritual teachers, whether Lithuanian universities will turn into the smithery of intellectuals.
Keywords: teacher; school; spiritual education; moral education